How to dis/articulate a system: repetition and difference in the work of Maria Lucia Cattani - Dimitrakaki, Angela (PORTO ARTE: Revista de Artes Visuais, 2016)
The article poses comments on the works by Maria Lucia Cattani, drawing from concepts such as repetition and difference and identification, in which the signs developed in the work reconfigure repetition and difference as two possibly overlapping territories in the space of art, in a work process unfolded in time.